Conflict transformation in South Africa : the impact of the Truth and Reconciliation Commission on social identity transformation - Kriel, Hennie (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Political Science))--Stellenbosch University, 2008.